1983
DOI: 10.1111/j.1365-2710.1983.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Hydrocortisone in a Zinc Oxidelotion

Abstract: SUMMARY An extemporaneous topical steroid formulation, prepared from a zinc oxide lotion and hydrocortisone lotion BPC, had poor stability. Hydrocortisone decomposed mainly to the 21‐aldehyde, but other degradation products were also identified by HPLC. The decomposition process could be described by first‐order kinetics. Stabilization methods employing pH adjustment, antioxidants and chelating agents were unsuccessful. The study emphasizes the dangers of diluting commercial formulations with unrecommended bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Several analytical methods such as LC-MS/MS 3 , HPLC [4][5][6][7][8] , and UV-spectrophotometric 9 methods have been reported for the estimation of acyclovir alone or with other drugs. In same way, many analytical methods like LC-MS/MS [10][11][12] , HPLC 13,14 and HPTLC 15,16 methods were available for the assay of hydrocortisone alone or with other drugs. The literature study did not revealed any reported method for simultaneous HPLC method for assay of acyclovir and hydrocortisone in dosage form.…”
Section: Introductionmentioning
confidence: 98%
“…Several analytical methods such as LC-MS/MS 3 , HPLC [4][5][6][7][8] , and UV-spectrophotometric 9 methods have been reported for the estimation of acyclovir alone or with other drugs. In same way, many analytical methods like LC-MS/MS [10][11][12] , HPLC 13,14 and HPTLC 15,16 methods were available for the assay of hydrocortisone alone or with other drugs. The literature study did not revealed any reported method for simultaneous HPLC method for assay of acyclovir and hydrocortisone in dosage form.…”
Section: Introductionmentioning
confidence: 98%
“…This situation represents a certain handicap for pharmacists who would like to prepare a particular formulation or dilute a commercial product with another vehicle or base. Most of the few reports concern hydrocortisone and, to a lesser extent, prednisolone (3)(4)(5). Good stability was generally found in petrolatum (6), commercial, slightly acidic O/W and W/O emulsions (6), and silicone fluid (3).…”
Section: Introductionmentioning
confidence: 99%
“…Poor steroid stability was also found in polyethyleneglycol (€9, absorption base (7), attapulgite suspension (9), and in zinc oxide-talc-glycerin lotions Correspondence: B. Gander, Department of Pharmaceutical Technology, University of Geneva, 30 quai Ernest-Ansermet, 121 1 Geneva 4, Switzerland. (4,6). Attempts to improve the stability of hydrocortisone in a zinc oxide lotion by pH adjustment or addition of antioxidants and chelating agents were unsuccessful (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instability of HC, when compounded in water or polyethylene glycol ointment bases has been previously demonstrated [2]. Likewise, HC has been shown to degrade when compounded in a zinc oxide vehicle [3]. The United States Pharmacopeia-National Formulary (USP-NF) has suggested guidelines regarding the beyond use date for such compounded formulations.…”
Section: Introductionmentioning
confidence: 99%